Epidemiology of HPB malignancy in the elderly. (March 2021) - Pericleous, Marinos; Khan, Shahid A.
Abstract: The incidence of hepatopancreatobiliary (HPB) cancers is increasing worldwide. Despite improvements in cancer surveillance and earlier access to therapy, these cancers still have poor survival rates, especially in elderly patients. There are several challenges in elucidating the epidemiology of these malignancies especially in view of the heterogeneous exposure to recognised risk factors and the coding systems used. Early diagnosis, crucial to improved survival, remains challenging as many patients present sporadically. Furthermore, the indolent nature of these tumours means they tend to present late, when curative treatments are no longer an option. Importantly, even when patients are diagnosed early and treated with curative intent, recurrence rates remain high. HPB cancers display a heterogenous molecular profile resulting in poorly effective systemic therapies in patients for whom curative treatments cannot be considered. Globally, people now live longer, and it is predicted that the population of individuals older than 85 will double by 2033. With increasing age comes increased cancer risk. There is a plethora of recognised challenges in elderly patients presenting with cancer and this is no different with HPB cancers. Complex co-morbidities including chronic disease, polypharmacy, cognitive decline and increasing psychosocial needs confer an extra layer of complexity in the management of this elderly sub population. The frailty that usually accompanies advancing age often means that patients take longer to recover and develop more complications after cancer therapies. In this article, we review the epidemiology of malignant HPB tumours with a focus on the elderly.